Hubungan Efikasi Diri dan Kecerdasan Emosional dengan Kecemasan dalam Praktek Kerja Industri pada Siswa SMK Negeri 1 Gunung Meriah - Wirda Hanim; Amanah Surbakti; Suryani Hardjo (Mahesa Research Center, 2022)
This study aims to determine the corellation between self-efficacy and emotional intelligence with anxiety in students of SMK Negeri 1 Gunung Meriah. Self-efficacy is a state of individual attitude to ensure himself that he will be able to carry out and complete certain tasks in various conditions Emotional intelligence is the ability to recognize oneself, be able to carry out social interactions and be able to adapt to the behavior of others. Anxiety is a feeling of fear and worry that is long-lasting on something that is not clear (subjective). The hypothesis proposed in this study is that there is a negative relationship between self-efficacy and emotional intelligence with anxiety. This study uses a quantitative approach. Sampling technique is total sampling, the sample is 143 students. The data collection method uses a Likert model scale. This study uses a scale of self - efficacy and emotional intelligence and anxiety scale . Multiple regression data analysis method. Based on the data analysis, it was obtained that Rxy) = -0.625 with p = 0.000 < 0.050, with BE% = 39.1%. Then based on the comparison of the two average values, it can be seen that self-efficacy is classified as low, meaning that the hypothetical (62.5) is greater than the empirical average (59.75) and the difference does not exceed the number one SD (11.674) and relative emotional intelligence. where the hypothetical mean (62.5) is greater than the empirical mean (61.31) and the difference does not exceed the number one SD (9.175) and moderate anxiety leads to high where the hypothetical mean (62.5) is smaller than the empirical mean (67, 43) and the difference does not exceed the number one SD (11,626). Thus, the proposed hypothesis is stated.